Structure based virtual screening of the Ebola virus trimeric glycoprotein using consensus scoring. (February 2018) - Onawole, Abdulmujeeb T.; Kolapo, Temitope U.; Sulaiman, Kazeem O.; Adegoke, Rukayat O.
Graphical abstract: Highlights: Consensus scoring method was used to combine the results of two docking programs. Trimeric glycoprotein structure of matured Ebola virus was used as target. Three compounds were selected from the consensus scoring result as potential hits. Hit SC-2 showed outstanding physicochemical properties and binding affinity. Abstract: Ebola virus (EBOV) causes zoonotic viral infection with a potential risk of global spread and a highly fatal effect on humans. Till date, no drug has gotten market approval for the treatment of Ebola virus disease (EVD), and this perhaps allows the use of both experimental and computational approaches in the antiviral drug discovery process. The main target of potential vaccines that are recently undergoing clinical trials is trimeric glycoprotein (GP) of the EBOV and its exact crystal structure was used in this structure based virtual screening study, with the aid of consensus scoring to select three possible hit compounds from about 36 million compounds in MCULE's database. Amongst these three compounds, (5R)-5-[[5-(4-chlorophenyl)-1, 2, 4-oxadiazol-3-yl]methyl]-N-[(4-methoxyphenyl)methyl]-4, 5-dihydroisoxazole-3-carboxamide (SC-2, C21 H19 ClN4 O4 ) showed good features with respect to drug likeness, ligand efficiency metrics, solubility, absorption and distribution properties and non-carcinogenicity to emerge as the most promising compound that can be optimized to lead compound against the GP EBOV. The binding mode showed that SC-2 is well embedded within the trimeric chains of the GP EBOV with molecular interactions with some amino acids. The SC-2 hit compound, upon its optimization to lead, might be a good potential candidate with efficacy against the EBOV pathogen and subsequently receive necessary approval to be used as antiviral drug for the treatment of EVD.